Writing a Blog Script to Promote Instant Cuko as Culinary Innovation from Palembang - Akhir Tanjung, Ahmad Khoirul; Rahma, Munaja; Ma’ruf, Zidni; Setyawati, Febriyani (English Department, Faculty of Humanities, Andalas University, 2024)
This final report aims to know how to write a blog script to promoteinstant cuko as culinary innovation from Palembang using Research andDevelopment (R&D) Method by Sukmadinata (2017). The method hasthree stages: (1) preliminary study; (2) model development; (3) finalproduct testing. The techniques of collecting the data were literature studyand interview. Then, the data was analyzed by classifying data, writing,and uploading the blog script. After collecting the information from theliterature study and field survey, the first draft of the blog script wasdeveloped based on Balkhi (2015) about the stages of structures in writinga blog script. The script of the blog contains the title, the introduction,the main body, and the conclusion. The blog script entitled “Instant Cukoas Culinary Innovation from Palembang” is a medium to promote instantcuko. The script is put in a blog and uploaded on Blogger. The blog helpstourists get information about instant cuko and aims to make it easy to bringcuko from Palembang. This research was conducted using the Research& Development approach with the Preliminary Study, Model Draft, andFinal Product Testing and Dissemination stages. Data was collectedthrough interviews, observations, and questionnaires. The research wasconducted in July-November 2023. The outputs of this research are finalreport, proceeding FIRST, scientific article published journals accreditedby SINTA, Blog Script, and partnership.